Late Pleistocene Great Bustards Otis tarda from the Maghreb, eastern Morocco - Cooper, Joanne H.; Collar, Nigel J.; Bouzouggar, Abdeljalil; Barton, Nick; Humphrey, Louise (Ibis (London, England), 2025)
The Moroccan population of the globally endangered Great Bustard Otis tarda is close to extinction. Although it is genetically distinct from the Iberian population, no evidence has been previously available to establish the age of its presence in Morocco. A radiocarbon‐dated assemblage of Great Bustards from the cemetery cave at Taforalt now confirms the species as a breeding resident of the Maghreb during the Late Pleistocene, ca. 14 700 years before the present. Furthermore, the remains reveal these birds to have been the subject of human exploitation and ritual behaviours. Recognition of the species' ancient status in Morocco reinforces the importance of this isolated and declining population and may help to add impetus to existing conservation efforts.